PEMAHAMAN TERHADAP KONSEP DOSA DAN PENGAMPUNAN DALAM KONTEKS KONSELING PASTORAL KRISTEN - Veronika Tangiruru; Sri Indra Yenni, Zhermita Grezya Pazcalya, Elfiance Sholla, Asrianto Asril (HUMANITIS: Jurnal Homaniora, Sosial dan Bisnis, 2023)
This research will analyze a deep understanding of the concepts of sin and forgiveness in the context of Christian pastoral counseling. Sin, as a central element in Christian theology, has various interpretations and implications in counseling practices. This study investigates the theological perspectives related to sin, including original sin and personal sin, and identifies the crucial role of Jesus Christ in the redemption and forgiveness of sins. Furthermore, this research explores the psychological impact of guilt arising from sin, as well as efforts to facilitate the acceptance of forgiveness in the pastoral counseling process. Through a comprehensive literature review, this research also discusses the strategies and counseling approaches applied to assist individuals in understanding and overcoming sin, as well as receiving forgiveness. These approaches encompass pastoral counseling methods that enable counselors to navigate wisely through the complexities of situations involving sin and forgiveness. Additionally, this research identifies potential obstacles in the process of understanding sin and forgiveness, and provides practical advice for pastoral counselors to facilitate repentance and spiritual growth in individuals. The results of this research are expected to provide valuable insights for pastoral counselors and church ministers in approaching, understanding, and guiding individuals experiencing conflicts or struggles related to sin and forgiveness. By integrating theological and counseling perspectives, this research establishes a solid foundation for pastoral care that is sensitive to the spiritual needs of individuals and strengthens spiritual bonds within the church community.